In situ digestibility of corn stover’ treated with fibrolytic enzymes (2017)
In situ digestibility of corn Stover fiber matrix treated with an enzymatic complex was studied by using two Swiss bulls (700 kg PV) with ruminant cannula. We used a randomized block design, where each animal constituted a block, and three enzyme levels: 0 g (TC), 1 g (T1), and 2 g (T2) of Fibrozyme® kg fodderl MS. The samples (5 g of dry matter in nylon bags) were incubated in the ruminant, and were extracted at 6, 12, 24, 48 and 72 hours after fermentation.Debasement was analyzed by a none lineal regression, using the P=a+b* (1-e-c* (t-to)) model. The soluble portion of the fibrous matrix, determined by washing the bags, resulted similar in both fiber fractions (FDN and FDA), with values of 0.50, 0.59 and 0.68 % respectively for each treatment. The degradability values of the insolvent, but degradable, fraction were: 37.28, 36.64 and 37.30 % for FDN, and 33.85, 35.07 and 41.19 % for FDA, with their three respective treatments.The T2 (FDN) and the TC (FDA) registered the highest degradation speed values (c %/h). The lag phase was approximately of 3.80, 4.90 and 4.80 h for FDN and 5.30, 5.30 and 4.90 h for FDA, with their three respective treatments. The FDN effective degradability (DE) oscillated between 19.70-14.40, 21.30-15.90 and 22.10-16.60 %; and the FDA, between 20.30-15.30, 21.10—15.80 and 23.40-17.30 %, in each one of the treatments, by using different ruminant exchange constants.The corn stover showed good degradation potential, over 39 % in FDN and 44 % in FDA, when treated with the highest levels of fibrolytic enzymes (T2). The results showed that an optimal usage of the fiber-matrix as energy source for the animal can be achieved, when enzymatic complexes are used in agriculture products and residues such as corn stover through its ruminal fermentation.